The Economic Impact of Organized Crime Infiltration in the Legal Economy: Evidence from the Judicial Administration of Organized Crime Firms - Francesca Calamunci; Francesco Drago (Institute of Labor Economics (IZA), 2020)
We analyze the economic consequences on firm profitability, performance, and investments of having another firm in the same market affiliated with a criminal organization. We do so by evaluating the spillover effects of a law providing the judicial administration of organized crime firms through the imposition of external managers in order to remove the connection to the criminal organization, and at the same time guarantee the continuity of production. By using detailed information on more than 180,000 companies, we exploit the firms' yearly variation in the exposure to criminal firms' judicial administration in their market (in the same province and industry). The empirical design allows us to control for confounding effects at the firm, market, and year levels. The results show that there is a large, positive spillover from the enforcement law, suggesting that the burden the organized crime firms impose on other firms is very large. Firms' performance and turnover increases by 2.2 and 0.7 percent, respectively, in the first four years after an organized crime firm enters the status of judicial administration. Investments measured by tangible and intangible assets increase with the number of firms entering into judicial administration by 0.75 percent. These results suggest that intensifying confiscation measures against criminal organizations has a strong positive effect on the economy.
Keywords: H00; H32; J00; K14; 330; organized crime; firm level data; policy evaluation